A Novel Approach for TCP for Regression Testing In Web Application - Priyanka P, Deshmukh; Vina M, Lomte (International Journal of Computer Sciences and Engineering, 2025)
For increase rate of fault detection test case prioritization is needed, which shows how fast bugs are identified during the testing phase. In test case prioritization follow way to use the information of previously executed test cases, such as coverage information, resulting in an iterative prioritization algorithm. Real fact of using coverage information can improve the rate of fault detection in prioritization algorithms. But performance of such iterative prioritization schemes degrade as the number of ties occurred in prioritization steps increases. In test case prioritization using lexicographical ordering and extended diagraph, we propose a new heuristic for breaking ties in coverage based techniques. Performance of the proposed technique in terms of the rate of fault detection is comparatively evaluated using a wide range of programs. Results indicate that the proposed technique can resolve ties and in turn noticeably increases the rate of fault detection.